2018
DOI: 10.20944/preprints201811.0585.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shape-memory Nanofiber Meshes with Programmable Cell Orientation

Abstract: This paper reports a rational design of temperature-responsive nanofiber meshes with shape-memory effect. The meshes were fabricated by electrospinning a poly(ε-caprolactone) (PCL)-based polyurethane with different contents of soft and hard segments. The effects of PCL diol/hexamethylene diisocyanate (HDI)/1,4-butanediol (BD) molar ratio in terms of the contents of soft and hard segments on the shape-memory properties were investigated. Although the mechanical property improved with increasing hard… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The drug release behavior Fig. 8 Application of SMPFs in cell culture: a SEM images of electrospun fibers before and after heating at 60 °C [102], b digital, SEM and cross-linked images of nanofibers before and after deformation and recovery process [102], c adhesion morphology and arrangement of human bone marrow mesenchymal stem cells [102], d before and after the shape and structure of the scaffold is changed, the cell viability on the scaffold with active strain arrangement is still very high [31] of SMPU/HA composite fibers was studied with DEX as drug model. The release amount increased with the increase of HA content, which was consistent with the change trend of degradation rate, as shown in Fig.…”
Section: Drug Releasementioning
confidence: 99%
See 1 more Smart Citation
“…The drug release behavior Fig. 8 Application of SMPFs in cell culture: a SEM images of electrospun fibers before and after heating at 60 °C [102], b digital, SEM and cross-linked images of nanofibers before and after deformation and recovery process [102], c adhesion morphology and arrangement of human bone marrow mesenchymal stem cells [102], d before and after the shape and structure of the scaffold is changed, the cell viability on the scaffold with active strain arrangement is still very high [31] of SMPU/HA composite fibers was studied with DEX as drug model. The release amount increased with the increase of HA content, which was consistent with the change trend of degradation rate, as shown in Fig.…”
Section: Drug Releasementioning
confidence: 99%
“…However, some studies have shown that cell culture on fiber scaffolds can change its morphology and better simulate the dynamic microenvironment. Niiyama et al [102] prepared a series of poly(εcaprolactone) (PCL)-based PU nanofiber nets with different ratios of soft and hard segments through electrospinning. SEM images before and after heating showed that the three samples were uniformly distributed in the form of fibers before heating (Fig.…”
Section: Cell Culturementioning
confidence: 99%
“…Another candidate SMP objects at micro/nanoscale to achieve the cyclic, thermomechanical test could be SMP micro/ nanofibers, which can be produced by electrospinning [93][94][95][96] Advances in Polymer Technology or wet spinning [97,98]. e shape-memory effect of fiber woven is usually investigated, and the woven can be used in smart textiles [99,100] or biomedical fields [101,102]. Although the SME of SMP woven is determined by knitted micro/nanofibers, physical entanglement and chemical connection play important roles as well.…”
Section: Smp Fibers At Micro-/nanoscalementioning
confidence: 99%